Unconscious Processes of Organizing: Intergroup Conflict in Mental Health Care - Mikkelsen, Elisabeth Naima; Gray, Barbara; Petersen, Anne (Journal of Management Studies, 2020)
AbstractA critical but overlooked issue in Weick’s seminal work,The Social Psychology of Organizing(1969/1979), concerns ‘the heat’ of organizing processes, namely, the underground emotional processes underpinning the organizing of conflictual work relationships. We present a qualitative case study of psychiatric agencies mandated by public policy to collaborate but instead engaged in persistent conflict despite its deleterious effects on their working relationship and on the wellbeing of the clients they intended to serve. To explain these conflictual features of organizing, we integrate Weick’s organizing theory with systems psychodynamics to deepen the understanding of emotions in organizing, specifically the motivational forces underpinning sensemaking and actions between interacting psychiatric agencies. This integration of theories reveals a critical feature of the relationship between the conscious and unconscious organizing processes: When a threat is involved, sensemaking and action are overtaken by social defences, resulting in dysfunctional organizing of the primary task. Drawing on these findings, we enrich Weick’s seminal work by developing a model that portrays organizing as the ritualized interaction of emotions, sensemaking and behavioural responses.